Factors Associated With Utilization Of Adolescent-Friendly Health Services In Sunsari District Of Nepal: Utilization Of Adolescent-Friendly Health Services - Usha Panta (STIKes Mandala Waluya Kendari, 2022)
Objectives: Adolescent friendly health services are the tailored health services for adolescents in a friendly environment where adolescents can easily and comfortably access and enjoy sexual and reproductive health services. Utilization of such services helps to address sexual and reproductive health problems faced by adolescents and the status of adolescent sexual and reproductive health (SRH) in Nepal is alarming. However, limited studies have been conducted on utilization of Adolescent Friendly Health Services and its associated factors among school adolescents. Thus, this study was carried out to assess the factors associated with utilization of adolescent friendly health services in Sunsari district of Nepal. Methods: This study was a descriptive, cross-sectional study carried out among 502 secondary school adolescents of grade 9 and 10 studying either in public or private schools of Inaruwa Municipality Sunsari District, Nepal. Single stage cluster sampling was followed in this study. Data was collected through administration of pre-tested semi-structured questionnaire during the period of January to March, 2022. Results : Regarding socio-demographic characteristics, majority of the participants were female (56.2%) compared to male (43.8%). Mean age of the participants was 15 years with standard deviation of 1.359 years and most (92.8%) of them followed Hinduism. More than half of the participants (54.0%) belonged to Madhesi ethnicity and most (61.0%) of them were from nuclear family. Likewise, majority (90.6%) of the adolescents were unmarried whereas 5.6 % were in relationship. More than three-fourth of the participants (79.5%) were staying with their parents. Most participants (53.2%) reported having very close relationship with their family. Similarly, majority (70.9%) of the adolescents had not seen the logo of adolescent friendly health services but three fourth (75.5%) of them had heard about adolescent friendly health services. Only 38.5% of participants were known about the availability of adolescent friendly health institution in their locality and more than three fourth (79.9%) of participants said that the time required to reach health facility was less than 30 minutes. Less than one fourth (24.1%) of the participants had felt needs for sexual and reproductive health services. The utilization of adolescent friendly health services among adolescents was low i.e., 14.5% (CI: 0.115-0.176) and more than half (54.8%) of them had used counselling services. Regards of preference, 44.4% of the participants stated that they preferred private health facilities and most of them (79.3%) preferred the health facility nearby their residence. Conclusion: Based on the findings of the study, different intervention programs could be conducted to increase the awareness about adolescent friendly health services among adolescents which may increase its utilization.